Electrical faults in high temperature superconducting power cables for MVDC power systems of all-electric ships. Issue 1 (March 2020) - Stamm, T; Choi, J H; Cheetham, P; Park, C; Kim, C; Graber, L; Pamidi, S
Abstract: High temperature superconducting (HTS) power cables are expected to be used in the future in electric ships that will have integrated power and energy systems (IPES). There have been a few studies on understanding electrical faults in power systems consisting of HTS cables; however, there are no comprehensive studies on the response of HTS cables for various types of electrical faults. We have recently initiated a research project on understanding various electrical faults in shipboard medium voltage direct current (MVDC) power systems and the duration of the fault, maximum voltage, and maximum current that the HTS cables will encounter during the fault. This paper presents investigations on the potential cable architectures being developed for MVDC power systems, and the type of faults that HTS cables will encounter in such systems. The paper will assess the relative merits of these architectures in terms of their suitability for accommodating the limitations of cryogenically cooled HTS cables and offer design suggestions for resilient power systems. Electrical and cryogenic thermal models of HTS cables that are suitable for assessing the response of HTS cables for electrical faults, as well as HTS cable designs that can endure electrical faults without catastrophic damage will also be discussed.